Analysis of Iron Content and Acceptability of Ambon Banana Cookies with Red Bean Flour Substitution - Vania Rifky Ardhita; Nur Fitri Widya Astuti; Septy Handayani (Indonesian Journal of Human Nutrition, 2025)
Iron deficiency anemia results in insufficient levels of hemoglobin in the blood. Iron levels can be improved by the consumption of snacks rich in iron. Bananas (Musa paradisiaca L.) and red beans are plant sources rich in iron and have the potential to enhance the nutritional value of cookies. The purpose of the study was to analyze differences in iron content and acceptability, determine the best formula, and provide consumption recommendations for cookies made with Ambon banana and red bean flour. This true experimental research used a post-test-only control design with a completely randomized design. This study involved semi-trained female panelists aged 19-25 years. Four cookie formulations in this study consisted of one control group and three treatment groups. One-way ANOVA statistical test results showed no significant difference (p = 0.446) in iron content, which ranged from 3.38-4.93 mg/100g. The Friedman statistical test results showed no significant difference in color (p = 0.722) and aroma (p = 0.808), but significant differences (p < 0.0001) were found in flavor and texture. Based on the Exponential Comparison Method, X2 formulation (80% wheat flour: 20% red bean flour) was identified as the best formula. According to the RDA recommendations, consuming 3-4 cookies can fulfill 10% of daily iron requirements for women.